ANALISIS KONFLIK BATIN TOKOH UTAMA DALAM NOVEL WANITA DI LAUTAN SUNYI KARYA NURUL ASMAYANI - Diana, Ani (JURNAL PESONA, 2016)
Literature discusses human in various aspects of life so through literature work people know individual personality, culture, and period. In novel Wanita di Lautan Sunyi created by Nurul Asmayani, it is figured out the different personality of three actors. The personality can be analyzed from the level of id, ego, and super ego. This study used descriptive qualitative method. The objective of this study is to know internal conflict that undergone by the main actor in this novel. In finishing each conflict happened by three main actors, the author describes it in simple, flow, and attractive. Moreover the use of well ordered and simple words make the story alive, seems as the real story so it is interesting to be read.Keywords: literature work, psychoanalysis, internal conflict.